An exploratory study on utilization of organic farming for sustainable agriculture at selected farms in Malaysia and India / Prasad a/l Vasudevon - Vasudevon, Prasad (2013)
Industrial agriculture has become the prominent agriculture system worldwide. In this system, farmers have become less dependent to environmental processes in shaping food production systems. They begin to adapt monoculture farming and rely on increasing quantities of agrochemicals, automated machineries, hybrid seeds and, more recently, Genetically modified crops. However, these practices have caused environmental consequences such as depletion of biodiversity, soil degradation, pollution and global warming. Furthermore concentration and vertical integration of corporate undermines farmer’s participation in the agrifood system. Farmers merely act as technology adopters and passive producers. In this system, farmers’ knowledge and innovations are impeded. In addition to this, heavy dependent on agrochemical and fuel increases production cost, thus reducing the farmer’s profit. Responding to these drawbacks, sustainable agriculture is proposed as an alternative to the industrial agriculture. Organic farming is a sustainable agriculture system. It is actively being promoted as an option toward achieving sustainable agriculture, all over the world, including in Malaysia. This thesis is an exploratory study to understand the origin, definition and principles of organic farming; to explore the practices on the ground and how it’s contributedto sustainable agriculturemodel and comply with the principles of organic farming; and finally to recommend few strategies for developing organic farming as a sustainable agriculture system in Malaysia. The origin, definition and principles of organic farming were studied through literature review. Organic farming practices were documented using qualitative case study method, in which semi-structured interviews, participatory observation, farm tours and secondary data collection were carried out with farmers, extension officers and non governmental iii organization (NGO) workers. Analysis of the observed practices shows that the practices fit into the sustainable agriculture model. The practices on the ground showed that organic farming is effective in providing environmental benefits, contributing for better economy for farmers, and improving the social status of farmers. Furthermore organic farms showed persistence and resilience as well. Observed practices also comply with principles of organic farming. Suggested strategies are supporting conversion to organic farming; building organic farming knowledge; enabling production of organic farming inputs; overcoming shortage of manpower; simplifying the certification process; assisting market development; and spreading the organic awareness. Observations showed organic farming is a suitable system to develop sustainable agriculture in Malaysia. However, because of the strong establishment of the industrial agriculture system in the country, mainstreaming organic farming will not be viable, therefore the way forward will be concentrating on the small holders who are cultivating non-commodity group and acceptance of a certain degree of flexibility in practice of organic farming principles.